Factors Affecting Learning Loss of Students in the Situation of Covid -19 of Schools under Phetchaburi Primary Educational Service Area Office 2 - Thungthong, Pairin; Boonsong, Kanchana (Journal for Developing the Social and Community, 2025)
Background and Aims: The COVID-19 pandemic has significantly impacted the education system, forcing a sudden shift in teaching and learning methods. Various factors have thus become key contributors to the learning loss experienced by students in educational institutions. The objective of this research was to study 1) the factors affecting the learning loss of students in schools under the Phetchaburi Primary Educational Service Area Office 2; 2) the level of students’ learning loss during the COVID-19 situation in schools under the Phetchaburi Primary Educational Service Area Office 2; and 3) the factors affecting students’ learning loss during the COVID-19 situation in schools under the Phetchaburi Primary Educational Service Area Office 2. Methodology: This study is quantitative research. The sample consisted of 274 teachers under the Phetchaburi Primary Educational Service Area Office 2, selected through multistage sampling. The research instrument was a five-point Likert scale questionnaire, which had a reliability coefficient of 0.943. The statistics used for data analysis included percentage, mean, standard deviation, and stepwise multiple regression analysis. Results: 1. The factors affecting students’ learning loss during the COVID-19 situation in schools under the Phetchaburi Primary Educational Service Area Office 2 were overall at a high level. When considering each aspect, the aspect with the highest mean score was teacher(X2), followed by school administrator (X5), technology (X4), student (X1), and family and environment (X3). 2) The overall level of students’ learning loss during the COVID-19 situation in schools under the Phetchaburi Primary Educational Service Area Office 2 was also at a high level. When considering each aspect, the aspect with the highest mean score was attribute learning loss(Y2), followed by academic learning loss (Y1). And 3) The factors affecting students’ learning loss during the COVID-19 situation in schools under the Phetchaburi Primary Educational Service Area Office 2 included technology (X4), student (X1), school administrator (X5), and teacher (X2). These factors accounted for 66.00 percent of the predictive power, with a standard error of estimate of 0.382. The predictive equation in raw score form was as follows: = 1.071 + 0.402 (X4) + 0.344 (X1) + 0.250 (X5) + -0.279 (X2) Conclusion: The overall findings indicate that the COVID-19 pandemic clearly led to learning loss among students in the area, affecting both learning characteristics and academic performance. Key contributing factors included technology, learners, school administrators, and teachers, all of which played a role in the changes to student learning during this crisis.